The relationship between pathologic nodal disease and residual tumor viability after induction chemotherapy in patients with locally advanced esophageal adenocarcinoma receiving a tri-modality regimen - McNamara, Michael J.; Rybicki, Lisa A.; Sohal, Davendra; Allende, Daniela S.; Videtic, Gregory M. M.; Rodriguez, Cristina P.; Stephans, Kevin L.; Murthy, Sudish C.; Raja, Siva; Raymond, Daniel; Ives, Denise I.; Bodmann, Joanna W.; et al. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Background: A complete pathologic response to induction chemo-radiotherapy (CRT) has been identified as a favorable prognostic factor for patients with loco-regionally advanced (LRA) adenocarcinoma (ACA) of the esophagus and gastro-esophageal junction (E/GEJ). Nodal involvement at the time of surgery has been found to be prognostically unfavorable. Less is known, however, about the prognostic import of less than complete pathologic regression and its relationship to residual nodal disease after induction chemotherapy. Methods: Between February 2008 and January 2012, 60 evaluable patients with ACA of the E/GEJ enrolled in a phase II trial of induction chemotherapy, surgery, and post-operative CRT. Eligibility required a clinical stage of T3-T4 or N1 or M1a (AJCC 6th). Induction chemotherapy with epirubicin 50 mg/m2 d1, oxaliplatin 130 mg/m2 d1, and fluorouracil 200 mg/m2/day continuous infusion for 3 weeks, was given every 21 days for three courses and was followed by surgical resection. Adjuvant CRT consisted of 50-55 Gy at 1.8-2.0 Gy/d and two courses of cisplatin (20 mg/m2/d) and fluorouracil (1,000 mg/m2/d) over 4 days during weeks 1 and 4 of radiotherapy. Residual viability (RV) was defined as the amount of remaining tumor in relation to acellular mucin pools and scarring. Results: Of the 60 evaluable patients, 54 completed induction therapy and underwent curative intent surgery. The Kaplan-Meier projected 3-year overall survival (OS) for patients with pathologic N0 (n=20), N1 (n=12), N2 (n=13), and N3 (n=9) disease is 73%, 57%, 35%, and 0% respectively (P75%, n=9) residual tumor viability was 67%, 42%, and 17% respectively (P=0.004). On multivariable analysis (MVA), both the pN descriptor and RV were independently prognostic for OS. In patients with less nodal dissemination (N0/N1), RV was prognostic for OS [3-year OS 85% (0-25% viable) vs. 51% (>25% viable), P=0.028]. Outcomes were poor, however, for patients with advanced nodal disease (N2/N3) regardless of RV [3-year OS 20% (0-25% viable) vs. 21% (>25% viable), P=0.55]. Conclusions: RV and the pN descriptor after induction chemotherapy are independent pathologic prognostic factors for OS in patients with LRA ACA of the E/GEJ. Patients with extensive nodal disease, however, have poor outcomes irrespective of residual tumor viability.